(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines the role of psychological factors that influence the formation of the product range. The essence of the concept of key signals and heuristics in the perception of the product range by consumers was determined, the degree of organization of the product display was investigated. Examples of empirical studies by foreign scientists regarding the impact of key signals on consumer perception of the assortment are described. Based on the above, the main conclusions made by scientists regarding the effective formation of the product range are systematized. Too much variety of products can confuse buyers. The results of the study showed that the reduction of the assortment did not affect the average level of its perceived variety. It is shown that consumers susceptible to promotions and special offers are prone to more analytical, detailed processing of information, are more sensitive to such a factor as the location of goods relative to each other, while for rational buyers, who often process information in a more holistic way, the color palette is more important. There are significant individual differences in how shoppers perceive the products on the shelf. Some people tend to process information holistically, while others are more detailed. The latter are greatly influenced by such a factor as the location of goods relative to each other. In addition, an organized presentation will make the difference in the number of options more obvious and significantly increase consumption. It was concluded that the following factors should be taken into account when forming a product assortment in a retail trade network: the buyer wants an organized presentation; do not give the buyer the opportunity to automatically filter part of the assortment; buyers mainly compare products located next to each other; one heuristic approach dominates; the situation of the purchase matters.